Analysis of Factors Affecting Company Value (Case Study on Startup Companies) - Dina, Ratna; Wattileo, Lidya Christine; Widhoyoko, Samuel Anindyo; Orlen, Aurellia (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the determinants of firm value among technology-based startup companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. The study employs a quantitative research design, utilizing secondary data obtained from financial statements and annual reports of ten eligible startup firms. The analysis is conducted using multiple linear regression via SPSS. The variables examined include Debt to Equity Ratio (DER), Return on Assets (ROA), Company Growth, and Company Size, with Tobin’s Q employed as a proxy for company value. The findings reveal that DER has a statistically significant positive effect on company value (p < 0.01), whereas ROA, company growth, and company size do not show significant influence. The results suggest that the capital structure, particularly debt utilization, plays a critical signaling role for investors in the startup ecosystem, while profitability and firm scale are less predictive of value at this early stage.